Response of packaging material and storage condition on postharvest quality of tuberose (Polianthes tuberosa) loose flowers (Current Horticulture, 2024)
The study was carried out at ICAR-Indian Agricultural Research Institute, New Delhi, to study the response of packaging  materials, viz. woven bag, high density polyethylene (HDPE) 51 micron , low-density polyethylene (LDPF) 25 micron, muslin  cloth bag and bamboo basket (control, without packaging) and two storage conditions, i.e. ambient condition (22) and cold  storage (or low temperature) condition (and 85-95% relative humidity) on keeping quality attributes of loose flowers of single  petalled tuberose (Polianthes tuberosa Linn.) cv. Arka Prajwal. Fully developed unopened florets were harvested in early  morning (before sunrise). The packaging and storage condition significantly influenced all parameters. Among all treatments,  loose flowers packed in HDPE 51 micron bag and stored under cold storage recorded maximum flower diameter (8.99 mm),  flower opening index (77.85%), colour (whiteness) index (89.13%) and shelf-life (6.00 day) of loose flowers under cold storage  condition. On the other hand, in control treatment the above said parameters recorded were 6.98 mm, 50.00%, 54.10% and  3.50 day, respectively. Under ambient condition, maximum flower diameter (8.08 mm), flower opening index (66.00%), colour  index (91.85%) and shelf-life (4.00 day) of flowers were recorded with HDPE 51 micron packaging. In control treatment, these  parameters were 6.73 mm, 50.00%, 63.77% and 1.50 days, respectively. Thus, it can be concluded that among packaging materials  HDPE 51-micron thickness bag was found to be the best for packing of loose flowers of tuberose cv. Arka Prajwal under both  ambient and cold storage conditions.
Keywords: High-density polyethylene; Loose flowers; Packaging material; Polianthes tuberosa; Storage condition